(untitled) (The Pakistan Development Review, 1998)
Saving, the fraction of national income that is not spent on current consumption, has long been widely regarded as a key factor in economic growth.1 The saving rate along with the incremental capital-output ratio determine the growth rate of the economy in the Harrod-Domar Model framework. The critical role of saving in capital accumulation and economic development is also recognised in the "two-gap" and classical growth models. For capital accumulation to result in sustained growth, it must be supported by adequate domestic/national savings. This has been clearly demonstrated by the extra-ordinary performance of the East Asian economies. While there have been brief periods of significant inflow of external financial resources to some developing countries in the past, foreign savings cannot be expected to provide a sustainable basis for financing domestic investment. Raising’ national saving rate is particularly essential to developing countries with a heavy debt service burden and limited capacity to obtain loans in foreign capital markets. The 1995 Mexican crisis showed, among other things, that low domestic savings can raise the probability of sudden capital outflows, and sharpen their negative consequences. In a financially integrated world, high national/domestic savings contribute to macro economic stability which is itself a powerful growth factor. Indeed, any macro economic adjustment programmes oriented to the resumption of long-run growth invariably emphasise the need to expand domestic savings.